Penguatan Identitas Budaya melalui Toponimi Danau Perintis sebagai Daya Tarik Wisata Edukatif di Desa Huluduotamo - Mohamad Karmin Baruadi; Sunarty Suly Eraku; Moch. Rio Pambudi (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Huluduotamo Village is developing Lake Perintis as a culture-based educational tourist attraction, but the local toponymic narrative is still predominantly oral, undocumented, and not yet integrated into the visitor experience. The Thematic Community Service Programme (April–June 2025) aims to explore and document the toponymy of Lake Perintis, strengthen the storytelling skills of residents, and provide digital interpretation media to support the preservation of cultural identity. The activities use a participatory-educational approach involving 32 participants (village government, traditional leaders, youth, community, and academics) through initial observation, perception/knowledge surveys, Focus Group Discussions (FGD) for narrative validation, interpretation content production, and dissemination. The programme produced (1) agreed cultural narratives from the FGD, (2) a destination interpretation content package combining historical/toponymic narratives, maps of important points, and visitor ethics, and (3) three QR codes installed at strategic points around the lake. Pre- and post-evaluations of participants showed an increase in understanding of toponymy and the importance of cultural preservation, accompanied by strengthened community participation in maintaining the cleanliness and environment of the destination. The integration of toponymy, storytelling, and QR codes enriches the learning experience of tourists while strengthening local cultural identity, making it a relevant strategy for sustainable educational tourism development in Huluduotamo Village.